Assessing advantages and disadvantages of macro- and micro-channel flow boiling for high-heat-flux thermal management using computational and theoretical/empirical methods. (April 2021) - Devahdhanush, V.S.; Lei, Yuchuan; Chen, Zhenqian; Mudawar, Issam
Highlights: Performances of two-phase micro- and macro-channels are compared Parametric trends for each are predicted using computational and analytical methods Micro-channels are shown to provide superior cooling performance Micro-channels incur much higher pressure drop and are more prone to choking Abstract: This study examines the advantages and disadvantages of micro- and macro-channel flow boiling for high-heat-flux cooling applications using both computational and theoretical/empirical methods. The computational simulations are conducted in ANSYS FLUENT using the Volume of Fluid (VOF) method along with the Lee phase change model, and accounting for both shear lift force and conjugate heat transfer along the channel walls. Computational results for both channel sizes are compared with theoretical/empirical results obtained using the Homogeneous Equilibrium Model (HEM) and Separated Flow Model (SFM), and both HEM and the Homogenous Frozen Model (HFM) are used to assess the potential for two-phase choking. The computational results show bubbles in micro-channels are highly confined and tend to grow longer in the flow direction. The two methods show good agreement in predicting wall temperatures. Overall, micro-channel heat sinks are shown to fare much better than macro-channels in terms of heat transfer performance, evidenced by both significantly higher heat transfer coefficients and lower wall temperatures, but this comes at the cost of significantly higher pressure drop and pumping power requirements. It is also shown micro-channels are prone to choking due to high two-phase Mach number.